An investigation of Fractional Mixed Functional Integro-Differential Equations with Impulsive Conditions - Kaliraj, K.; Aswini, U.; Ravichandran, C.; Logeswari, K.; Nisar, Kottakkaran Sooppy (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, we derived the existence of mild solutions for fractional functional mixed integro-differential equations in Banach spaces. Standard fixed point techniques are used to obtained the results. Initially, we first formulate the definition of PC-mild solution and we prove the existence of solutions for the considered fractional system. Finally, we present an example to demonstrate the obtained theoretical results.